Reliability-Based Assessment of Galloping Instability of Thin-Walled Steel Beams - Nguyen, Huu Anh Tuan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Galloping instability relating to cross-wind vibrations can be found in flexible and lightly damped structures. In the present paper, the reliability of a thin-walled steel beam in maintaining its galloping stability was examined using a probabilistic approach. The analysis considered random variation in the cross-sectional geometrical properties of the beam, the material elastic modulus, the structural damping and the wind speed. A large number of Monte Carlo simulations were performed with normal and Gumbel distributions applied to the random variables to determine the probability distribution function of the safety margin.
Keywords: instability; wind speed; Monte Carlo simulation; Reliability Index ß; safety factor; niestabilność; prędkość wiatru; wskaźnik niezawodności ß; współczynnik bezpieczeństwa